The Effectiveness of the Manpower and Transmigration Office (DISNAKERTRANS) Function in Reducing Unemployment in Sukabumi Regency - Distia Nur Sakinah; Tuah Nur; Dian Purwanti (Program Pascasarjana Universitas Negeri Makassar, 2023)
The purpose of this research is to find out the FUNCTIONAL EFFECTIVENESS OF THE WORKFORCE TRANSMIGRATION DINAS IN REDUCING THE UNEMPLOYMENT RATE IN SUKABUMI DISTRICT. Unemployment is someone who does not have a job, is looking for work, or is preparing for work. Generally, the cause of unemployment is the imbalance between population growth and employment, meaning that the number of workers is greater than the number of jobs. Based on the termination of employment recorded at the Sukabumi District Manpower and Transmigration Office by the Indonesian Employers Association (APINDO) for 19,700 people from 2019 to 2022, in the 2018–2019 period, the Sukabumi Open Unemployment Rate was in the range of 7-9%. Whereas in 2020, the Sukabumi Regency Open Unemployment Rate increased to 9.60%, in addition to the Sukabumi Regency Open Unemployment Rate in 2021 of 9.51%. (BPS West Java, 2022). This research used qualitative research methods that were analyzed with a descriptive approach. Descriptive research is conducted to determine independent variables without making comparisons or connecting one variable to another. Data collection techniques used by researchers include observation, interviews, and documentation. The results of research on the effectiveness of the function of the Manpower and Transmigration Office in reducing unemployment in Sukabumi Regency can be measured using the three dimensions proposed by Duncan in Sterrs (2020: 53) regarding organizational effectiveness, namely: goal achievement, integrity, and adaptation.Keywords: Effectiveness, Function, and Unemployment of the Department of Manpower and Transmigration (Disnakertrans) of Sukabumi District